What Caused the 1991 Currency Crisis in India? - Saxena, Sweta; Cerra, Valerie (Washington, D.C. : International Monetary Fund, 2000)
Did real overvaluation contribute to the 1991 currency crisis in India? This paper seeks an answer by constructing the equilibrium real exchange rate, using an error correction model and a technique developed by Gonzalo and Granger (1995). The results are affirmative and the evidence indicates that current account deficits and investor confidence also played significant roles in the sharp exchange rate depreciation. The ECM model is supported by superior out-of-sample forecast performance versus a random walk model.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet